Analisis Load Balancing Menggunakan Metode Pcc (Per Connection Classifier) Pada Badan Pengelolaan Keuangan Dan Aset Daerah (Bpkad) Kabupaten Bogor - Sujiliani Heristian Sujiliani; Septiyan Dwi Cahyo (LPPM Universitas Bina Sarana Informatika, 2023)
Along with the increasing human need for information technology, the development of information technology is increasingly spurred. This development is in line with advances in information technology and computer networks that use technology that applies automation to the system. Internet connection at the Regional Financial and Asset Management Agency Kab. Bogor uses 2 Internet Service Providers. When one of the ISPs experiences a problem, the internet service will be disrupted and must be configured manually. The purpose of writing this final project is to keep the internet connection stable and not interfere with employee performance. The writing of this final project uses the methods of interview, observation, and literature study. The purpose of this study is how the author applies load balancing techniques that can overcome problems related to connection paths from 2 ISPs. One solution to deal with this problem is to use the method per connection classifier. The per connection classifier allows routers to remember the incoming and outgoing data paths that were passed at the beginning of the connection traffic. By implementing the load balancing technique using the per connection classifier method, it is hoped that the internet connection will be stable and not interfere with the performance of the employees.